Constant Gravitational Mass of Moving Object and Variational Gravitational Field Deducing that Application Scope of General Theory of Relativity is Limited (Global Journal of Science Frontier Research, 2014)
This paper, based on simple examples, aims to show that the gravitational mass of an object is constant and that the distribution of gravitational field is associated with the motion of object. The formula for distribution of gravitational field during the motion of object has been deduced through variation in geometrical relation between gravitational lines. The paper analyzes the difference between gravitational mass and inertial mass of moving object in terms of size and direction and concludes that equivalency principle is false and application scope of general theory of relativity is limited.
Keywords: gravitational mass; gravitational field; gravitational flux; axiom of constant force balance; general theory of relativity; black hole